Effect of Gabapentin on Sexual Function in Vulvodynia: A Randomized, Placebo-controlled Trial. Issue 2 (February 2019) - Bachmann, Gloria A.; Brown, Candace S.; Phillips, Nancy A.; Rawlinson, Leslie A.; Yu, Xinhua; Wood, Ronald; Foster, David C.
Abstract : (Abstracted from Am J Obstet Gynecol 2019;220:89.e1–89.e8) Vulvodynia is a chronic pain syndrome characterized by symptoms such as stinging, burning, irritation, or itching of the vulva. Women with vulvodynia experience deficits across all aspects of sexual function.